2021
DOI: 10.1016/j.jns.2021.119866
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on acute stroke care-data analysis from the RES-Q registry 2020 in N. Macedonia

Abstract: Background and aimsIn March 2020, WHO declared Novel Coronavirus Disease (COVID-19) outbreak to be a pandemic. All countries were given the call to take prompt actions to reduce spread of infection and save lives. The prevalence of the disease rose exponentially worldwide. When it comes to the new SARS COVID 19, the understanding of the disease was poor, especially among the non-medical folk. Social media was flooded with information and several of them were not tested for authenticity. Accurate information is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although a few groups report large prolongations, mainly driven by the hospital saturation delaying the diagnostic and therapeutic processes [ 33 , 39 ], most report decreases (which may be explained by the need to ensure available beds to attend more patients coming from the emergency departments) or no differences [ 40 43 ]. In our study we found a slight increase in length of stay (near 3 hours), although we did not conduct an analysis on the specific reasons for this mild increase.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few groups report large prolongations, mainly driven by the hospital saturation delaying the diagnostic and therapeutic processes [ 33 , 39 ], most report decreases (which may be explained by the need to ensure available beds to attend more patients coming from the emergency departments) or no differences [ 40 43 ]. In our study we found a slight increase in length of stay (near 3 hours), although we did not conduct an analysis on the specific reasons for this mild increase.…”
Section: Discussionmentioning
confidence: 99%